Performance of a Standardized Clinical Assay for Urinary C–C Motif Chemokine Ligand 14 (CCL14) for Persistent Severe Acute Kidney Injury. Issue 7 (28th July 2022) - Koyner, Jay L.; Chawla, Lakhmir S.; Bihorac, Azra; Gunnerson, Kyle J.; Schroeder, Rebecca; Demirjian, Sevag; Hodgson, Luke; Frey, Jennifer A.; Wilber, Scott T.; Kampf, J. Patrick; Kwan, Thomas; McPherson, Paul; et al.
Key Points: Using a standardized assay, we provide operating characteristics for two cutoffs for urinary C-C motif chemokine ligand 14 (CCL14) for the prediction of persistent severe AKI. A CCL14 cutoff of 1.3 ng/ml identifies 91% of patients who developed persistent severe AKI, need for RRT, or death, with a negative predictive value of 92%. In multivariable analyses, a CCL14 >13 ng/ml was associated with 10.4 adjusted odds for persistent severe AKI, need for RRT, or death ( P <0.001). Visual Abstract: Abstract : Background: Clinical use of biomarkers requires the development of standardized assays and establishment of cutoffs. Urinary C-C motif chemokine ligand 14 (CCL14) has been validated to predict persistent severe AKI in critically ill patients with established AKI. We now report on the performance of standardized cutoffs using a clinical assay. Methods: A second aim of the multicenter RUBY Study was to establish two cutoffs for the prediction of persistent severe AKI (defined as KDIGO stage 3 AKI for at least 72 consecutive hours). Patients who received renal replacement therapy (RRT) or died before achieving 72 hours in stage 3 AKI were also considered to have reached the end point. Results: A cutoff value for urinary CCL14 of 1.3 ng/ml was determined to achieve high sensitivity (91%; 95% CI, 84% to 96%), and 13 ng/ml achieved high specificity (93%; 95% CI, 89% to 96%). The cutoff of 1.3 ng/ml identifies the majority (91%) of patients who developed persistent severe AKI with a negative predictive value of 92%. The cutoff at 13 ng/ml had a positive predictive value of 72% (with a negative predictive value of 75%). In multivariable adjusted analyses, a CCL14 concentration between 1.3 and 13 ng/ml had an adjusted odds ratio (aOR) of 3.82 (95% CI, 1.73 to 9.12; P =0.001) for the development of persistent severe AKI compared with those with a CCL14 ≤1.3 ng/ml, whereas a CCL14 >13 ng/ml had an aOR of 10.4 (95% CI, 3.89 to 29.9; P <0.001). Conclusions: Using a clinical assay, these standardized cutoffs (1.3 and 13 ng/ml) allow for the identification of patients at high risk for the development of persistent severe AKI. These results have immediate utility in helping to guide AKI patient care and may facilitate future clinical trials. Clinical Trial registry name and registration number: Identification and Validation of Biomarkers of Acute Kidney Injury Recovery, NCT01868724